Early Detection of Escherichia coli Producing Extended Spectrum Beta Lactamase (ESBL) in Cattle Farm Waste from Urban Jakarta - Aulia Maulida; Syafitri Jumianto; Riris Lindiawati Puspitasari, S.Si., M.Si (Prosiding Seminar Nasional Pemberdayaan Masyarakat (SENDAMAS), 2025)
This study examined the presence of Escherichia coli resistant to third-generation cephalosporins in cattle manure originating from an urban farming area in South Jakarta. The study aimed to detect presumptive extended-spectrum beta-lactamase (ESBL)-producing E. coli using total plate count analysis, selective culture, Gram staining, and biochemical identification. Urine and fecal waste samples were collected from a cattle farm located in close proximity to residential settlements. Samples were cultured on MacConkey Agar supplemented with cefotaxime, followed by Gram staining and IMViC biochemical tests. All isolates showed lactose-fermenting colonies with pink to red coloration on MacConkey Agar, Gram-negative rod morphology, and biochemical characteristics consistent with E. coli (Indole positive, Methyl Red positive, Voges–Proskauer negative, Citrate negative). Total bacterial counts reached approximately 10³ colony-forming units per milliliter, with fecal samples exhibiting higher bacterial loads than urine samples. Bacterial growth on cefotaxime-supplemented media indicated phenotypic resistance to third-generation cephalosporins, suggesting the presence of presumptive ESBL-producing strains. These findings demonstrate that urban cattle manure may serve as a reservoir of antibiotic-resistant bacteria and highlight the need for confirmatory ESBL testing, strengthened antimicrobial resistance surveillance, and the implementation of integrated One Health strategies to mitigate environmental and public health risks.Keywords – Antimicrobial Resistance; Cattle Farm Waste; Cephalosporin Resistance; Escherichia Coli; Urban Livestock.